(Re)knowing the dimension of health management in a medical curriculum - Rodrigues, Luciane Cristine Ribeiro; Julian, Carmen Maria Casquel Monti [UNESP]; Damiance, Patrícia Ribeiro Mattar; Garbellotti, Thayná Maria (University of Minho, 2022)
In Brazil, there is a significant representativeness of doctors in institutional administrative positions, however, some of them work without general or specific knowledge of public administration bases and health management. Based on this assumption, the objective was to present a geographical, administrative and pedagogical characterization of medical courses in Brazil and, in particular, in the state of São Paulo, identifying how the theme of health management is worked on in these courses, as well as understanding the experience of health professors regarding the expression of health management in a medical curriculum. It is a quantitative and qualitative research. This article presents the results of two of the quantitative phases and a part of the qualitative phase, in which 38 teachers from an institution belonging to the municipal higher education network participated. The prevalence of the private administrative entity and the semester school regime was observed in the analyzed courses. It was not possible to categorically state that themes related to health management are effectively addressed in medical degrees in the state of São Paulo. However, theachers professors who participated in this study recognize the value of conceptual, procedural and attitudinal contents of health management in the initial training of doctors. It is concluded that it is necessary to consider the relation between the National Curriculum Guidelines for undergraduate Medicine in Brazil and the pedagogical practice, the administrative intentionality and the training perspectives of medical education managers, indicating the steps to be followed for the design and the execution of structured curriculum, in the area of health management.
(Re)conhecendo a dimensão da gestão em saúde em um currículo médico